Peningkatan Pemasaran UMKM Kopi melalui Pelatihan dan Pendampingan Digital Marketing - Maulana Irfani, Muhamad Irfan; Siswanto, Siswanto (Mafapress Institut Pesantren Mathali'ul Falah Pati, 2024)
Micro, Small and Medium Enterprises (UMKM) are one form of business activity that can expand employment opportunities and provide economic benefits with a wide scope to the community. This Community Service Activity aims to Increase the marketing of coffee MSMEs through digital marketing in Tempur Village, Keling District, Jepara Regency. In addition, for branding Tempur Coffee. The community service approach is carried out using the PLA (Participatory Learning and Action) approach method. With the assets that have been owned in the form of human resources (HR) in the form of coffee producers or MSMEs that are collected in the coffee cluster community of Tempur Village, Keling District, Jepara Regency.